2019
DOI: 10.1007/s11142-019-09506-y
|View full text |Cite
|
Sign up to set email alerts
|

Changes in analysts’ stock recommendations following regulatory action against their brokerage

Abstract: Despite the importance of sell-side analysts in the capital markets, we know little about the effectiveness of routine monitoring of the sell-side industry. We examine the attributes of sell-side research issued by analysts before and after their brokerage is subject to regulatory sanctions. We find that after a regulatory action, analysts at sanctioned brokerages lower their stock recommendations, both in absolute terms and relative to the recommendations of other analysts following the same firms. Following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…10 Although analyst forecasts in I/B/E/S are not identified by name, I/B/E/S files with stock recommendations contain abbreviated names of brokers (e.g., RAYMOND) and the names of following analysts (e.g., Long D). For this reason, more recent empirical studies with a focus on the advisory industry examine sell-side research quality using as a proxy only the bias in stock recommendations (e.g., Call et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Although analyst forecasts in I/B/E/S are not identified by name, I/B/E/S files with stock recommendations contain abbreviated names of brokers (e.g., RAYMOND) and the names of following analysts (e.g., Long D). For this reason, more recent empirical studies with a focus on the advisory industry examine sell-side research quality using as a proxy only the bias in stock recommendations (e.g., Call et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, more recent empirical studies with a focus on the advisory industry examine sell‐side research quality using as a proxy only the bias in stock recommendations (e.g., Call et al. 2019).…”
mentioning
confidence: 99%
“…Therefore, the study suggested a set of recommendations to reduce the negative effects of the cost stickiness, enhance the stock price informativeness, improve the effectiveness of the capital market, and the efficiency of allocating resources in the capital market . ‫السابقة‬ ‫األدبيات‬ ‫أن‬ ‫على‬ ‫عالوة‬ (e.g., Weiss, 2010;Ciftci et al, 2016;Huang et al, 2017;Banker et al, 2016 (Ibrahim, 2018;Özkaya, 2021;Li & Luo, 2021;Xu & Wang, 2022) ، ‫لزوجة‬ ‫ظاهرة‬ ‫بتفسير‬ ‫أخرى‬ ‫دراسات‬ ‫قامت‬ ‫حين‬ ‫في‬ ‫التكاليف‬ ‫التعديل‬ ‫تكاليف‬ ‫لنظرية‬ ‫وفقا‬ ‫بالشركة‬ ‫والمحيطة‬ ‫السائدة‬ ‫والتنظيمية‬ ‫االقتصادية‬ ‫والظروف‬ ‫الحوكمة‬ ‫وأليات‬ ‫الوكالة‬ ‫ونظرية‬ (Chen et al, 2012;Ezat, 2014;Ibrahim, 2015;Magheed, 2016 (Yezegel, 2015;Cheng et al, 2016;Call et al, 2019;Serafeim & Yoon, 2022 (Banker et al, 2018) .…”
Section: Introductionmentioning
confidence: 99%
“…Analysts are the representatives of rational investors and have great influence on other investors (Driskill et al, 2020). Analysts release forecast analysis reports to help investors form more accurate ideas about the impact of current earnings on future company performance, enhance the information content of stock prices (Gleason and Lee, 2003;Jegadeesh and Kim, 2006;Cheng et al, 2016;Huang et al, 2016), improve the effectiveness of capital market (Lys and Sohn, 1990;Easley and O' Hara, 2004;Loh and Stulz, 2018) and the resource allocation efficiency of capital market (Schipper, 1991;Call et al, 2019). Cost stickiness increases the volatility of earnings, reduces the accuracy of analysts' forecasts, and significantly affects investors' judgments and decisions and the information valuation process of capital market.…”
mentioning
confidence: 99%